Money in the Apophthegmata Patrum - Milewski, Ireneusz (Studia Ceranea, 2019)
The objective of this paper is to discuss accounts related to money in Apophthegmata Patrum, a collection of sayings attributed to famous Egyptian monks. The collection as we know it was produced in the 6th century. By describing the organisation of monastic centres in Egypt in the 4th and 5th century Apophthegmata also offer us some information about the period’s economic aspects. However, by and large, the data is very general. It pertains to: prices, wages, tax issues as well as money that was given to monks by pilgrims. Limited as it is, the data confirms that money was present in the everyday lives of Egyptian monks in late antiquity. Naturally, the major consideration behind whether a monk possessed money was whether he had contact with the outside world. This included selling self-made handcraft at markets, particularly woven mats and ropes, clay pots and sometimes also more specialised items (such as copied codices of the Bible). In Apophthegmata Patrum, similarly to what is the case with other Early Byzantium hagiographic texts, we find little information about moral evaluation of money or about the “appropriate” way to manage it.